Practical experience of the acid and bacterial underground leaching of uranium at the Semizbay field - A. K. Naravas (Известия высших учебных заведений: Геология и разведка, 2016)
The discovery and investigation of the uranium field Semizbay are considered. The main parameters of lithological filtration inhomogeneity as well as geotechnological properties of the ore-bearing rocks are defined in terms of their influence on the borehole underground leaching of uranium. Works on the acid-bacterial underground leaching of uranium give positive results on two experimental cells. Carbonate ores have not significant influence on the process of the underground leaching.